Data protection during the coronavirus crisis. (11th August 2020) - Schneble, Christophe Olivier; Elger, Bernice Simone; Martin Shaw, David
Abstract : Smartphone apps to track SARS‐CoV 2 infections need to fulfill certain minimal requirements to guarantee privacy and justify their use under data protection laws.